Effects of SGLT2 inhibitors on the intestinal bacterial flora in Japanese patients with type 2 diabetes mellitus - Kusunoki, Masataka; Hisano, Fumiya; Matsuda, Shin-ichi; Kusunoki, Akiko; Wakazono, Naomi; Tsutsumi, Kazuhiko; Miyata, Tetsuro (Drug Research, 2023)
Selective inhibitors of sodium glucose co-transporter-2 (SGLT2) suppress renal glucose reabsorption and promote urinary glucose excretion, thereby lowering blood glucose. SGLT2 inhibitors have been reported to reduce body weight. However, the mechanism underlying the reduction in the body weight induced by SGLT2 inhibitor treatment remains to be elucidated. In this study, we investigated the effects of SGLT2 inhibitors on the intestinal bacterial flora. A total of 36 Japanese patients with type 2 diabetes mellitus received a SGLT2 inhibitor (luseogliflozin or dapagliflozin) for 3 months, and the prevalences of balance-regulating bacteria and balance-disturbing bacteria in the feces of the patients before and after SGLT2 inhibitor treatment were determined. SGLT2 inhibitor treatment was associated with a significant increase of the overall prevalence of the 12 types of balance-regulating bacteria. In addition, significant increases in the prevalences of the short-chain fatty acid (SCFAs)-producing bacteria among the balance-regulating bacteria were also observed. Individual analyses of the balance-regulating bacteria revealed that the SGLT2 inhibitor treatment was associated with a significant increase in the prevalence of Ruminococci, which are balance-regulating bacteria classified as SCFAs-producing bacteria. However, SGLT2 inhibitor had no effect on the balance-disturbing bacteria. These results suggested that SGLT2 inhibitor treatment was associated with an overall increase in the prevalence of balance-regulating bacteria. Among the balance-regulating bacteria, the prevalences of SCFAs-producing bacteria increased. SCFAs have been reported to prevent obesity. The results of the present study suggest that SGLT2 inhibitors might induce body weight reduction via their actions on the intestinal bacterial flora.
Keywords: SGLT2 inhibitor; intestinal bacterial flora; obesity; balance-regulating bacteria; short-chain fatty acid-producing bacteria